The Utilization of Gadget in Maintaining Prophetical Values in Millennial Generation - Muyasaroh (International Journal of Psychosocial Rehabilitation, 2020)
Facts in a society of changing times which are followed by social changes are getting faster. Consumptive nature that puts technology forward in various fields as one of the characteristics of millennial generation makes them experience social transformation and lifestyle drastically. The use of favorable Gadget can be used to maintain predictive values such as Humanity, Liberation, and Transcendence, which have also changed their implementation. The Faculty of Islam under the auspices of the University of Muhammadiyah Gresik is one of the highest educational institutions in the education system. The students are of productive age and technology users, especially Gadget, as the hallmark of the millennial generation who are the focus of the discussion. Thus, this Filed Research study uses qualitative methods with observation data collection techniques, and interviews are then analyzed with steps to reduce data, display data, and conclusions and Verification. The results of this study describe the profile of FAI students as the millennial generation in maintaining predictive values through the use of the Gadget and maintaining the Value of student transcendence utilizing Gadget and its application for the study of wisdom, motivation to migrate to the Koran, implementation of the Koran for memorization, while maintaining the Value of humanization more on aspects of news distribution Up to date about humanity and withdrawal of social funds more easily with Gadget and to maintain the Value of Liberation in cyberspace that is to re-check the truth of a news. So that predictive values always exist in every era and generation.